Helicobacter pylori Infection and Strain Types in Adult Dyspeptic Patients Undergoing Endoscopy in a Specialized Hospital of Dhaka City - Rahman, Sufi HZ; Rahman, M Anisur; Arfin, MS; Alam, M Mahbub; Bhuiyan, TM; Ahmed, Nasim; Nahar, Shamsun; Hassan, MS (Bangladesh Journal of Medical Microbiology, 2009)
Helicobacter pylori infection occurs worldwide with a high prevalence in developing countries. Virulence of H. pylori strains varies in different geographic regions. The aim of this study was to see H. pylori infection and its strain types in adult dyspeptic patients in Bangladesh and to analyze association of H. pylori strain types with clinical disease and severity of histological gastritis. Ninety consecutive adult dyspeptic patients undergoing diagnostic endoscopy were tested for H. pylori infection by culture, rapid urease test (RUT), histology and anti H. pylori IgG ELISA (Enzyme linked immunosorbent assay). H. pylori strain types were determined by Western Blot analysis. Association of strain types with clinical gastro-duodenal diseases and grades of histological gastritis were analyzed by χ2 test. Among the selected patients, 53 (58.9%) were culture positive, 48 (53.3%) were RUT positive, 31 (34.4%) were histology positive and 82 (91.1%) were anti-H. pylori IgG ELISA positive. By Western Blot analysis of the 90 sera samples, 48 (53.3%) showed antibodies to Type I strain of H. pylori, 21 (23.3%) Intermediate strain and 3 (3.3%) Type II strain. Endoscopically, 20 (22.2%) patients were found normal, 27 (30.0%) had gastritis, 9 (10.0%) had duodenitis, 28 (31.1%) had peptic ulcer disease, 4 (4.4%) had gastric carcinoma, and 2 (2.2%) had reflux esophagitis. Histologically, 34.4% had H. pylori, 44.4% had polymorhonuclear neutrophil (PMN), 100% had mononuclear cell (MNC) infiltration of different grades, 1.1% had atrophic gastritis and 2.2% had intestinal metaplasia of moderate grade. H. pylori strain types was not associated with clinical gastro-duodenal diseases or grades of PMN or MNC infiltration (p > 0.05) in these patients. Key words: Helicobacter pylori infection, H. pylori strain types, gastro-duodenal diseases, grades of gastritis doi: 10.3329/bjmm.v3i1.2963 Bangladesh J Med Microbiol 2009; 03 (01): 4-9